(untitled) (International Journal of Biology and Chemistry, 2019)
In this review a complex signaling in human neurofibromatosis type 2 (NF2) in nervous system and other tissues is discussed. The neurofibromatosis type 2 (Nf2) gene, known as a tumor suppressor, encodes a protein Merlin, which is closely related to the ezrin, radixin, and moesin (ERM) proteins of the band 4.1 protein superfamily. Mutations of the NF2 gene cause an autosomal dominant disorder neurofibromatosis type 2 (NF2). Merlin’s function as a growth suppressor depends on its structural conversion from an inactive to an active form caused by changes in its phosphorylation status. Depending on its structural conformation Merlin binds to numerous interacting proteins, which are either required for Merlin’s tumour suppressor function or impair Merlin’s growth suppressor activity contributing to tumorigenesis. Despite significant progress made in the NF2 study for the last two decade, the molecular mechanisms of the tumor suppressor function of Merlin are still little understood. Loss of the Nf2 function leads to aberrant activation of receptor tyrosine kinases (RTK) and the downstream mitogenic signaling pathways. Overexpression of ErbB receptors has been reported in NF2-related and sporadic vestibular schwannomas (VS) and many other human cancers. Studies have shown that inhibition of the ErbB family RTKs can serve as an alternative approach for the treatment of sporadic and NF2-related VS through inhibition of ERK1/2 and PI3K/AKT signaling pathways. Preclinical and clinical studies of the potential therapeutic targets for the treatment of VS, and other brain tumors are underway. A better understanding of Merlin’s deregulated signaling in NF2 can provide useful therapeutic strategies for treatment of human VS and other brain tumors.